Conhecimentos e práticas de profissionais de saúde na prevenção do suicídio na cidade de Foz do Iguaçu - Pinto, Meire Perpétua Vieira (2018)
Introduction. Suicide is considered by researchers a multidetermined, complex phenomenon, existing since antiquity. Suicidologists emphasize the importance of developing studies making feasible the implementation of programs that bring closer health professionals and people who present behaviors at risk of suicide. Objective: To understand how physicians, psychologists, nurses, nursing technicians and community agents of Basic Care in a triple border region identify and develop care actions for people with suicidal behavior. Methodology: Study based on Alfred Schütz'sSocial Phenomenology developed in the city of Foz do Iguaçu-PR, Brazil in Basic Health Care Units. The participants' reports were collected from June 2017 to December 2017 through a semi-structured interview, with the following guiding questions: Tell me what you know about suicide and about suicide prevention. Do you know the National Guidelines for the Prevention of Suicide? Do you assist or have assisted people with suicidal behavior? Comment, from your experience, what do you understand about Care and about Care Actions? Do you develop caregiving actions for people with suicidal behavior? If so, which ones? If not, why? In your opinion, what actions could be taken with this population? What are your expectations regarding the Networks of Care with this population? Results: There are three categories unfolded in nine subcategories related to "because motive", the past/present experiences of the professionals and another category that unfolds in five subcategories related to "in-order-to motive", that is, their expectations towards the future. Final Thoughts: The collective construction fostered by the actions of permanent education can contribute to the expansion of the understanding of suicide, not only as an individual issue, but as a social problem that requires collective and community coping solutions, extensive to other social actors. The study evidenced the reflections on the difficult daily life experienced by health professionals, when faced with their own anguish related to impotence facing such a complex and challenging phenomenon for the whole society.